Pencegahan Perundungan Anak Dengan Memanfaatkan Teknologi Digital Studi Kasus UPTD SPF SDN Nangkaan Bondowoso - Dewanto, Wahyu Kurnia; Arifianto, Aji Seto; Rakhmad, Hariyono; Firmansyah, Muhammad Hafidh; Kasiyati, Kasiyati (P3M Politeknik Negeri Jember, 2025)
Bullying among students is increasingly prevalent, driven by various factors, including environmental influences and the impact of globalization. This issue poses significant challenges for teachers, who are often expected to monitor all students throughout the school day despite limited resources and time. The aim of this study is to explore effective strategies for preventing bullying in schools by integrating technological and creative approaches. The research employs a mixed-methods approach, combining quantitative analysis of bullying incidents with qualitative data from interviews and observations. The study focuses on the implementation of CCTV technology to enhance student behavior monitoring and prevent bullying incidents. Additionally, it investigates the use of arts-based activities as a means to help students channel excess energy into positive, creative outlets, thus reducing the likelihood of engaging in bullying behavior. The findings suggest that the combination of technological supervision and arts-based interventions significantly reduces the incidence of bullying in schools. The conclusion emphasizes the effectiveness of a holistic approach that incorporates both advanced monitoring tools and emotional support activities, highlighting the potential for these strategies to create a safer and more supportive school environment where students can thrive both emotionally and socially.